Analyzing Hospital Transfers Using INTERACT Acute Care Transfer Tools: Lessons from MOQI. Issue 9 (12th June 2019) - Popejoy, Lori L.; Vogelsmeier, Amy A.; Alexander, Greg L.; Galambos, Colleen M.; Crecelius, Charles A.; Ge, Bin; Flesner, Marcia; Canada, Kelli; Rantz, Marilyn
Abstract : OBJECTIVES: We explored the differences in potentially avoidable/unavoidable hospital transfers in a retrospective analysis of Interventions to Reduce Acute Care Transfers (INTERACT) Acute Transfer Tools (ACTs) completed by advanced practice registered nurses (APRNs) working in the Missouri Quality Improvement (QI) Initiative (MOQI). DESIGN: Cross‐sectional descriptive study of 3996 ACTs for 32.5 calendar months from 2014 to 2016. Univariate analyses examined differences between potentially avoidable vs unavoidable transfers. Multivariate logistic regression analysis of candidate factors identified those contributing to avoidable transfers. Setting: Sixteen nursing homes (NHs), ranging from 120 to 321 beds, in urban, metro, and rural communities within 80 miles of a large midwestern city. PARTICIPANTS: A total of 5168 residents with a median age of 82 years. MEASUREMENTS: Data from 3946 MOQI‐adapted ACTs. RESULTS: A total of 54% of hospital transfers were identified as avoidable. QI opportunities related to avoidable transfers were earlier detection of new signs/symptoms (odds ratio [OR] = 2.35; 95% confidence interval [CI] = 1.61‐3.42; P < .001); discussions of resident/family preference (OR = 2.12; 95% CI = 1.38‐3.25; P < .001); advance directive/hospice care (OR = 2.25; 95% CI = 1.33‐3.82; P = .003); better communication about condition (OR = 4.93; 95% CI = 3.17‐7.68; P < .001); and condition could have been managed in the NH (OR = 16.63; 95% CI = 10.9‐25.37; P < .001). Three factors related to unavoidable transfers were bleeding (OR = .59; 95% CI = .46‐.77; P < .001), nausea/vomiting (OR = .7; 95% CI = .54‐.91; P = .007), and resident/family preference for hospitalization (OR = .79; 95% CI = .68‐.93; P = .003). CONCLUSION: Reducing avoidable hospital transfers in NHs requires challenging assumptions about what is avoidable so QI efforts can be directed to improving NH capacity to manage ill residents. The APRNs served as the onsite coaches in the use and adoption of INTERACT. Changes in health policy would provide a revenue stream to support APRN presence in NH, a role that is critical to improving resident outcomes by increasing staff capacity to identify illness and guide system change. J Am Geriatr Soc 67:1953–1959, 2019